2016
DOI: 10.1016/j.pedn.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Neonatal Nursery Design on Mothers' Interactions in the Nursery

Abstract: Mothers and nurses perceived that the SFR nursery enhanced privacy and maternal closeness for mothers compared to the OB nursery. However, the SFR nursery design presented challenges to some interactions of value to nurses and mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 36 publications
0
27
0
2
Order By: Relevance
“…This subscale of the family-centered care measure assesses privacy and the extent to which a parent feels welcome and "not like a visitor". Qualitative work indicates that SFR mothers experience greater ownership over both their space and the care of their infant [39], and this may apply to small pods such as those at our study site. Parents identify having their presence welcomed by staff and amenities for them as factors that foster presence [40], suggesting that respect from staff and presence might be related.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This subscale of the family-centered care measure assesses privacy and the extent to which a parent feels welcome and "not like a visitor". Qualitative work indicates that SFR mothers experience greater ownership over both their space and the care of their infant [39], and this may apply to small pods such as those at our study site. Parents identify having their presence welcomed by staff and amenities for them as factors that foster presence [40], suggesting that respect from staff and presence might be related.…”
Section: Discussionmentioning
confidence: 86%
“…We found no difference between units. In contrast, an Australian survey reported that OW mothers had greater support from nurses than SFR mothers [39], and indepth interviews revealed that in the SFR unit both mothers and nurses considered it more difficult to initiate interactions compared to in one large space where others were visible. Further examination of nurse support in units of differing design is warranted to better understand how to optimize support in different environments.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This subscale of the family-centered care measure assesses privacy and the extent to which a parent feels welcome and "not like a visitor". Qualitative work indicates that SFR mothers experience greater ownership over both their space and the care of their infant (40), and this may apply to small pods such as those at our study site. Parents identify having their presence welcomed by staff and amenities for them as factors that foster presence (41), suggesting that respect from staff and presence might be related.…”
Section: Discussionmentioning
confidence: 86%
“…In our qualitative study in the SFRs of this unit parents described how privacy allowed them to learn to care for their infant without feeling scrutinized (42). Nurses have observed that SFR mothers "know more and do more" and in turn are more confident and prepared for discharge compared to OW mothers (40).…”
Section: Discussionmentioning
confidence: 95%